The Effect Of Price Discounts And Online Customer Ratings On Grabfood Consumer Loyalty On Salero Restaurant, South Jakarta - Mar’i, Idzan Ihdil; Layaman; Jaelani, Aan (Cirebon International Journal of Economics and Business, 2024)
Technological developments have resulted in the creation of online food delivery services that allow consumers to order food without having to come to the location. Efforts need to be made to maintain loyalty to consumers who use Grabfood services. The purpose of this study is to determine the effect of price discounts and online customer ratings on Grabfood consumer loyalty at Salero Restaurant. The research method used is a quantitative approach with an associative research type. Data collection was carried out using a questionnaire. The number of samples in this study was 100 respondents. The determination of respondents used a purposive sampling method with the following criteria: (1) respondents are users of Grabfood services on the Grab application, and (2) respondents have ordered Grabfood at the Salero Restaurant Merchant in South Jakarta at least once. The results of the study show that: (1) price discounts have a significant effect on Grabfood consumer loyalty at Salero Restaurant with a calculated tvalue > t table, namely 6.213 > 1.985. (2) Online customer ratings have a significant effect on Grabfood consumer loyalty at Salero Restaurant with a calculated t value > t table, namely 4.830 > 1.985. (3) Price discount and online customer rating simultaneously have a significant effect on Grabfood consumer loyalty at Salero Restaurantwith a calculated f value > f table, namely 56.783 > 3.09.